2011
DOI: 10.2174/187152711798072310
|View full text |Cite
|
Sign up to set email alerts
|

Role of Resveratrol and its Analogues in the Treatment of Neurodegenerative Diseases: Focus on Recent Discoveries

Abstract: Neurodegenerative diseases are a group of chronic, progressive disorders characterized by the gradual loss of neurons in several areas of the central nervous system (CNS). Substantial evidence has documented a common inflammatory mechanism in neurodegeneration. It is known that classical anti-inflammatory agents, steroids and nonsteroidal anti-inflammatory drugs, have not played a major role in the management of CNS inflammatory conditions. This may be partly due to the natural compartmentation of the brain by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…This result is in accordance with the previous studies [26][27][28][29][30], whereas the SLM function was significantly reversed in the resveratrol treated against aluminum along with fluoride-treated group as compared to the aluminum along with fluoride-treated group, showing the protective effect of resveratrol. This observation is in agreement with the earlier findings showing protection of resveratrol against neurodegeneration and preserves cognitive function [31][32][33]. Resveratrol alone treated group did not show any changes as compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in accordance with the previous studies [26][27][28][29][30], whereas the SLM function was significantly reversed in the resveratrol treated against aluminum along with fluoride-treated group as compared to the aluminum along with fluoride-treated group, showing the protective effect of resveratrol. This observation is in agreement with the earlier findings showing protection of resveratrol against neurodegeneration and preserves cognitive function [31][32][33]. Resveratrol alone treated group did not show any changes as compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, 22 out of the 26 selected genes whose expression is significantly affected by the use of RSV are down-regulated. Therefore, it seems that the reported beneficial effect of RSV in CNS alterations [see [17] for review] correlates with simultaneous reduction of the expression of different genes. Network analysis showed that among interconnected genes (under moderate stringent parameters) all but Pkp4 were down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Other family members of carotenoid cleavage enzyme in bacteria and fungi cleave resveratrol to produce 4-hydroxy-benzaldehyde and 3,5-dihydroxy-benzaldehyde ( 45,46 ). Notably the 4 ′ hydroxyl group of resveratrol has been identifi ed as crucial for antioxidant and neuroprotective effects of stilbenoids ( 47 ). It seems likely that other stilbenoids may serve as ring precursors of Q.…”
Section: Discussionmentioning
confidence: 99%